Natural Jute Laminate for the Improvement of Strength Properties of Concrete Specimen - ZULFIKAR, Achmad Jusuf; YAAKOB, Mohd Yuhazri; UMARFARUQ, Hel Mee; SYAH, Rahmad (Engineering Transactions, 2023)
In the last decade, the exploration and investigation of natural ingredients as alternative materials for metal substitutes have been continuously conducted to produce eco-friendly products with sufficiently good strength. The climate and geography of countries like Indonesia provide that such materials are available abundantly and can be easily replanted. Thus, these materials have considerable potential for application in various products. The purpose of this study is to analyze the compressive and tensile strength of a cylindrical column concrete structure reinforced externally with laminate composite materials derived from jute fabric sheets. The specimen manufacturing method uses a vacuum bagging technique with the specimen size specified in the ASTM C39 test standard. After manufacturing, the specimens underwent the treatment of immersion in clean water for 28 days, followed by drying at room temperature for additional 28 days. The column concrete specimens were wrapped with laminate composite materials with variations in several layers of jute fabric. Compressive strength and splitting tensile tests were conducted according to ASTM C39 and ASTM C496 test standards, respectively. The test results showed that applying laminate composite sheaths on the outer surface of the column concrete structure resulted in an increase in strength of up to 100% for both compressive strength and splitting tensile strength. The magnitude of such an increase in strength is reported in this article.